Application of high-speed camera measurements for determination of energy losses generated in a vibrating belt of CVT transmission - Łatas, Waldemar; Kot, Adam (Bulletin of the Polish Academy of Sciences Technical Sciences, 2023)
The paper presents a proposition of the theoretical-experimental method of determination of power losses in the transversely vibrating rubber V-belt of continuously variable transmission. The article comprises the results of experimental tests conducted on a special test stand with a complete scooter drivetrain powered by a small two-stroke internal combustion engine. Such a configuration allows ensuring real CVT working conditions. A high-speed camera was used for the contactless measurement of belt vibrations and time-lapse image analysis was performed in dedicated software. An axially moving Euler–Bernoulli beam was assumed as the mathematical model. Longitudinal vibrations and nonlinear effects were omitted. Additionally, it was assumed that the belt material behaves according to the Kelvin–Voigt rheologic model. Analysis of the damped free vibrations of the cantilever beam, made of the belt segment, allowed to determine the equivalent bending damping coefficient. The CVT power losses, due to bending in the rubber transmission belt, were obtained for the fixed working conditions after numerical calculations. The proposed methodology is a new approach in this research area, which allows to obtain results impossible to achieve with other measurement methods.